2011
DOI: 10.1016/j.ijgo.2011.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Advancing obstetric and neonatal care in a regional hospital in Ghana via continuous quality improvement

Abstract: Maternal and newborn mortality were reduced in a low-resource setting when appropriate models for continuous quality improvement were developed and employed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 15 publications
1
37
0
Order By: Relevance
“…This observation may partly be explained by differences in implementation of national health policies and programs in conjunction with the disparities in additional programs implemented in the regions; examples of such regional differences are the Kybele program in the Greater Accra region (13, 14), kangaroo mother care (55), UNICEF-sponsored ACSD (15) in Northern Ghana, High Impact Rapid Delivery (HIRD) (56), and Project Five Alive (57, 58). The variation may also be driven by differences in baseline rate of neonatal mortality across the regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation may partly be explained by differences in implementation of national health policies and programs in conjunction with the disparities in additional programs implemented in the regions; examples of such regional differences are the Kybele program in the Greater Accra region (13, 14), kangaroo mother care (55), UNICEF-sponsored ACSD (15) in Northern Ghana, High Impact Rapid Delivery (HIRD) (56), and Project Five Alive (57, 58). The variation may also be driven by differences in baseline rate of neonatal mortality across the regions.…”
Section: Discussionmentioning
confidence: 99%
“…The FANC pursues improvement in maternal and child survival through individualized antenatal care that entails a comprehensive assessment of pregnant women in terms of their socio-cultural beliefs, lifestyle, and medical characteristics to improve early detection and treatment of illness and pregnancy complications. In addition to these national programs and policies, various regions also implemented different intervention programs, for example, the Kybele program in the Greater Accra region (13, 14), Accelerated Child Survival and Development (ACSD) (15) sponsored by United Nation Children and Education Fund (UNICEF) in the Northern, Upper East, and Upper West regions, and Kangaroo Mother Care (KMC) (16) which commenced in six regions in 2007. Although the deadline for the attainment of MDG 4 has elapsed, 99% of childhood mortality still occurs in LMICs (5, 17), with Africa accounting for about 50% (18).…”
Section: Introductionmentioning
confidence: 99%
“…In 2007, Kybele, Inc., a US-based humanitarian organization, began a 5-year partnership with the Ghana Health Service (GHS) to reduce maternal and newborn mortality (13). Ridge Regional Hospital (RRH) in Accra was selected as the primary target facility, because it was the largest GHS hospital in the country.…”
Section: Background and Rationalementioning
confidence: 99%
“…The large hospitals received a high volume of obstetric and surgical cases and were plagued by delay resulting from too many patients and too few resources. This in turn led to high mortality rates (8, 12, 13). …”
Section: Introductionmentioning
confidence: 99%
“…Best use of resources should probably be guided by the project implementation plans already described by groups such as Kybele and CARE. 6,8,11,12 These projects have shown that the starting point should be assessment and improvement of local infrastructure and resources to acceptable levels, before clinical training and building technical competence are initiated, while looking to establish partnerships with local centers of excellence and training departments. A 2009 editorial highlighted the benefits of the Kybele view that 2 weeks of hands-on training is superior to didactic lectures in obstetric anesthesia.…”
mentioning
confidence: 99%